2009
DOI: 10.1596/1813-9450-5077
|View full text |Cite
|
Sign up to set email alerts
|

Remittance Stability, Cyclicality And Stabilizing Impact In Developing Countries

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…For small island economies, they found that, while larger remittance flows tended to reduce output volatility, remittances played an important role in transmitting international business cycles (Jackman, Craigwell, and Moore, 2010). By contrast, Neagu and Schiff (2009), using a sample of 116 countries, find that remittance flows have been destabilizing or have had no effect on output volatility in 80 percent of the countries they examined.…”
Section: Remittance Flowsmentioning
confidence: 94%
“…For small island economies, they found that, while larger remittance flows tended to reduce output volatility, remittances played an important role in transmitting international business cycles (Jackman, Craigwell, and Moore, 2010). By contrast, Neagu and Schiff (2009), using a sample of 116 countries, find that remittance flows have been destabilizing or have had no effect on output volatility in 80 percent of the countries they examined.…”
Section: Remittance Flowsmentioning
confidence: 94%
“…They showed that remittances appear to be stabilizing in more cases than official aid. Neagu and Schiff (2009) compared the cyclically and stabilizing impacts of ODA, FDI and remittances. They suggest that it seems effective to separately examine counter-cyclical and stabilizing effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If, on the other hand, migrant workers are self-interested, remittances will respond positively to improved economic conditions in the country of origin, as to take advantage of business opportunities. Some studies have found evidence of altruistic remittances (Chami et al [15] and Frankel [16]), others of self-interest remittances (Barajas et al [17] and Neagu and Schiff [18]), some studies that it depends on the country being examined (Durdu and Sayan [19]). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Equation (18) indicates that money growth in the economy depends on the existing stock of money M t and the monetary injection implemented by the central bank X t . The monetary growth factor θ t is specified as an AR(1) process as follows:…”
Section: The Central Bank the Money Stock Evolves According Tomentioning
confidence: 99%